Correlation between duration of chronic renal failure patients undergoing hemodialysis and sensorineural hearing loss - Novi Primadewi; Dewi Pratiwi; Taufani Dewi (Oto Rhino Laryngologica Indonesiana, 2022)
ABSTRACTBackground: Along with the increasing incidence of chronic renal failure patients receiving hemodialysis, recently, the incidence of sensorineural hearing loss (SNHL) among patients with end-stage kidney disease undergoing hemodialysis had also increased. The cochlea and kidney have many anatomical, physiological, pharmacological and pathological similarities. Dialysis sometimes causes worsening of hearing function. Objective: To determine the correlation between the duration of renal failure patients undergoing hemodialysis and the degree of sensorineural hearing loss. Method: A retrospective study using cross sectional method, conducted from August–September 2018. The study began by identifying patients with chronic renal failure and then continued with Oto Acoustic Emission (OAE) examination and pure tone audiometry. Result: The results of the Spearman rank statistical test for the correlation between duration of hemodialysis and the degree of SNHL in the right and left ears in patients with chronic renal failure found a significant positive correlation r= 0.498 and p=0.001 (right) , and r= 0.400 and p=0.006 (left). Conclusion: There was a significant correlation between the length of hemodialysis and the degree of sensorineural hearing loss. ABSTRAKLatar belakang: Seiring dengan peningkatan angka kejadian pasien gagal ginjal kronik yang mendapatkan hemodialisa, akhir-akhir ini didapati peningkatan angka kejadian Sensorineural Hearing Loss (SNHL) di antara pasien dengan penyakit ginjal stadium akhir yang menjalani hemodialisa. Koklea dan ginjal memiliki banyak kesamaan anatomis, fisiologis, farmakologis dan patologis. Dialisa terkadang menyebabkan memburuknya fungsi pendengaran. Tujuan: Untuk mengetahui hubungan lama pasien gagal ginjal yang menjalani hemodialisa dengan derajat gangguan pendengaran tuli sensorineural. Metode: Penelitian retrospektif dengan metode potong lintang, dilakukan dari Agustus-September 2018. Penelitian dimulai dengan mengidentifikasi pasien gagal ginjal kronik kemudian dilanjutkan dengan pemeriksaan tes Oto Acoustic Emission (OAE) dan audiometri nada murni. Hasil: Hasil uji statistik Spearman rank untuk korelasi lama hemodialisa dengan derajat SNHL telinga kanan dan kiri pada pasien gagal ginjal kronik didapatkan korelasi positif yang signifikan: r= 0,498 dan p=0,001 (kanan) dan r= 0,400 dan p=0,006 (kiri). Kesimpulan: Terdapat korelasi yang bermakna antara lama hemodialisis dengan derajat tuli sensorineural.